King Palm Frond Development as Fashion Product using Modular Interlocking System - Desita Rizky Kusumaningtyas; Mochammad Charis H; Kristian Eka (Universitas Pendidikan Indonesia (UPI), 2022)
Fashion is one of the most developed creative industry sub-sectors in Indonesia which is part of the creative economy program. The development of materials and models for fashion products is increasingly diverse, one of which is the use of Indonesian natural materials. In Indonesia, the types of varieties of palm plants are very diverse, this is supported by the tropical climate, so there are so many of them because they can be easily cultivated. The part of the palm tree that is most often discarded is the frond, therefore the use of natural materials such as palm fronds will be very useful, especially as fashion . One of the zero waste technique modular interlocking. Collecting data in this experimental research is an interactive method, by conducting in-depth interviews and product observations. In this experimental research using quantitative methods to obtain data regarding the tastes of[GJ1] users. From the processing of palm fronds, what will be used as a material substitute for fashion products is the product of a purse, purse or what can be called a clutch with a unique palm fiber using a modular interlocking technique.